Implementation of UNSCR 1325 Women, Peace, and Security in the Democratic Republic of the Congo (DRC) Through the National Action Plan 2019-2022 - Salfa Risdalina; Inayah Divia; Januari Pratama Nurratri Trisnaningtyas (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The purpose of this paper is to eradicate sexual violence committed by members of the Congolese Police and to address sexual violence in the DRC, particularly by fighting impunity and providing protection for victims and witnesses. This paper analyzes the implementation of UNSCR 1325 in the DRC through the lens of the WPS framework. A qualitative research method is employed, using literature study as the primary data collection technique. The result is that implementation of the NAP is structured around four WPS pillars including participation, prevention, protection, relief and recovery. In the participation pillar, efforts include appointing women to legislative institutions and revising electoral laws. The prevention pillar focuses on disarmament, demobilization, and recovery programs. The protection pillar emphasizes safeguarding the rights of women with disabilities, indigenous women, and survivors of sexual violence. The relief and recovery pillar centers on gender mainstreaming in peace processes. The suggestion is to improve the effectiveness of the NAP implementation in Congo, the government needs to allocate an adequate national budget to avoid dependence on external donors. Oversight of policy implementation must be strengthened, particularly in legal protection and the prevention of gender-based violence. Furthermore, it is crucial to eradicate patriarchal culture through gender equality education and expand psychosocial recovery services in conflict-affected areas.